2022
DOI: 10.15282/ijame.13.2.2016.11.0283
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of high velocity impact performance of carbon nanotube and lead reinforced magnesium alloy

Abstract: This paper presented the effect of strain rate changes due to Carbon Nanotube (CNT) and Lead addition in Magnesium Alloy, AZ31B on high velocity impact performance. This metal is normally used to fabricate armored vehicle panel. The changing strain will affect the strain rate and had been widely used in automotive applications to accommodate high velocity impact. High strain rate material was applied on the armored vehicle to withstand the impact of the projectile. AZ31B alloy was reinforced with CNT and Lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Thus, it is important to properly determine the behaviour and properties of new materials to be used in these vehicles. Incorporating existing materials with lightweight materials such as composites, aluminium foam and aluminium alloys has become of interest nowadays [2][3][4]. Aluminium and its alloys are among materials widely used to achieve lightweight construction and improve vehicle crashworthiness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to properly determine the behaviour and properties of new materials to be used in these vehicles. Incorporating existing materials with lightweight materials such as composites, aluminium foam and aluminium alloys has become of interest nowadays [2][3][4]. Aluminium and its alloys are among materials widely used to achieve lightweight construction and improve vehicle crashworthiness.…”
Section: Introductionmentioning
confidence: 99%
“…Adding CNT alone without optimal value may decreased the energy absorption capability as the introduction of insufficient CNT will make the material prone to molecule sliding [8]. As mention from the previous studies, the presence of CNT and Pb had proven to affect the material behavior in term of ballistic impact [9,10], thus energy absorption performance. Mention that their several to enhance magnesium alloy such heat treatment such as annealing, quenching, normalizing and so on [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…They found that at increasing strain rates, tensile properties are strain rate dependent. For magnesium alloys, Abdullah et al [7] reported that these alloys were capable of withstanding high speed impacts that performed using the Split Hopkinson pressure bar tester. However, the trend of tensile properties at low to intermediate strain rates for extruded AZ31 and AZ61 magnesium alloys are still unknown.…”
Section: Introductionmentioning
confidence: 99%